Defined by Relationship : A Conversation with Charles Foster. - Burton, Howard (Ideas Roadshow Conversations Ser., 2021)
This book is based on an in-depth filmed conversation between Howard Burton and Charles Foster, who is a writer, traveller, veterinarian, barrister, philosopher and Fellow of Green Templeton College, University of Oxford. This wide-ranging conversation provides a detailed exploration of several of his books in many different fields with a particular focus on ""Human Dignity in Bioethics and Law"" and the New York Times Bestseller ""Being a Beast"" .This carefully-edited book includes an introduction, At the Heart, and questions for discussion at the end of each chapter. Howard Burton was the F.